Private Infrastructure : Activity Down by 13 Percent in 2003 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Drawing on the Bank's Private Participation in Infrastructure Project Database, this Note reviews developments in 2003. Data for the year show that investment in projects with private participation, totaled almost U$S 50 billion - back to 1994 levels. About 100 projects reached financial closure. Electricity was the only sub-sector - and, East Asia, and the Middle East and North Africa, the only developing regions - that saw private activity grow in 2003.